Tidal turbine performance in the offshore environment - Fleming, C; Conor Fleming (2014)
A three dimensional computational model of a full scale axial flow tidal turbine has been used to investigate the effects of a range of realistic environmental conditions on turbine performance. The model, which is based on the Reynolds averaged Navier-Stokes equations, has been developed using the commercial flow solver ANSYS Fluent. A 1:30 scale tidal turbine is simulated in an open channel for comparison to existing experimental data. The rotor blades are directly resolved using a body-fitted, unstructured computational grid. Rotor motion is enabled through a sliding mesh interface between the rotor and the channel boundaries. Reasonably good agreement in thrust and power is observed. The computed performance curves are offset from the measured performance curves by a small increment in rotor speed. Subsequently, a full scale axial flow turbine is modelled in a variety of conditions representative of tidal channel flows. A parametric study is carried out to investigate the effects of flow shear, confinement and alignment on turbine performance, structural loading, and wake recovery. Mean power and thrust are found to be higher in sheared flow, relative to uniform flow of equivalent volumetric flow rate. Large fluctuations in blade thrust and torque occur in sheared flow as the blade passes through the high velocity freestream flow in the upper portion of the profile and the lower velocity flow near the channel bed. A stronger shear layer is formed around the upper portion of the wake in sheared flow, leading to enhanced wake mixing. Mean power and thrust are reduced when the turbine is simulated at a lower position in a sheared velocity profile. However, fluctuations in blade loading are increased due to the higher velocity gradient. The opposite effects are observed when the turbine operates at greater heights in sheared flow. Flow misalignment has a negative impact on mean rotor thrust and power, as well as on unsteady blade loading. Although the range of unsteady loading is not increased significantly, additional perturbations are introduced due to interactions between the blade and the nacelle. A deforming surface is introduced using the volume-of-fluid method. Linear wave theory is combined with the existing free surface model to develop an unsteady inflow boundary condition prescribing combined sheared flow and free surface waves. The relative effects of the sheared profile and wave-induced velocities on turbine loading are identified through frequency analysis. Rotor and blade load fluctuations are found to increase with wave height and wave length. In a separate study, the performance of bi-directional ducted tidal turbines is investigated through a parametric study of a range of duct profiles. A two dimensional axi-symmetric computational model is developed to compare the ducted geometries with an unducted device under consistent blockage conditions. The best-performing ducted device achieves a peak power coefficient of approximately 45% of that of the unducted device. Comparisons of streamtube area, velocity and pressure for the flow through the ducted device shows that the duct limits the pressure drop across the rotor and the mass flow through the rotor, resulting in lower device power.